Advancing the notion of maslow hierarchical needs theory into retirement village sustainability needs - Sharifah Rahama Amirul; Asmah Alia Mohamad Bohari; Farah Ajlaa Julaihi; Mohd Azrai Azman; Kuryati Kipli (Malaysian Construction Research Journal, 2022)
The retirement village (RV) sector is booming and expanding its market as the world's ageing population has grown in recent years, notably in industrialised and developing countries. RV refers to a high-quality housing facility for retirees wanting to continue living independently in a safe and comfortable environment during post-retirement. In response to the demands of a sustainable development, sustainability of RV has been one of the critical focuses in existing literatures. Thus, this paper aims to advance the notion of Maslow hierarchical needs theory into the setting of retirement villages. The proposed framework of this paper offers a structured and thorough understanding of aged elderly requirements and aspirations; starting with the most fundamental of aged requirements and progressing to the highest desire of having a high quality of life during their golden years, which presents unique prospects for making a theoretical contribution to the requirements of the ageing population and improving RV sustainability.